Choice reaction time and subsequent mobility decline: Prospective observational findings from The Irish Longitudinal Study on Ageing (TILDA) - Chintapalli, Renuka (EClinicalMedicine, 2020)
BACKGROUND: Cognitive and motor function in ageing are intertwined, but whether slower motor response time (MRT) to a cognitive stimulus could herald accelerated mobility decline is unknown. Using data from The Irish Longitudinal Study on Ageing (TILDA), we examined whether slower MRT may predict a greater than expected increase in Time Up and Go (TUG) after 4 years. METHODS: Participants aged 50 years or older were divided into two groups based on their mean MRT (< 250 ms versus ≥ 250 ms). A repeated measures ANOVA compared TUG trajectories between groups, controlling for baseline age, sex, height, education level, mini mental-state examination (MMSE) score, self-reported vision and hearing, medical conditions (cardiovascular, cerebrovascular disease, diabetes), and number of medications. FINDINGS: At Wave 1, 1982 (58.7%) had a mean MRT of < 250 ms, with a mean TUG of 8.1 s (SD 1.6); and 1397 (41.3%) had an MRT of ≥ 250 ms, with a TUG of 9.0 s (SD 2.2). At Wave 3, TUG increased to 8.8 s (SD 2.0) and 10.2 s (SD 3.9), respectively. The results of the adjusted repeated measures ANOVA suggested that there was a statistically significant interaction between MRT group and Wave (P = 0.023, η(2)(p) = 0.002). INTERPRETATION: TILDA participants in the slower MRT group seemed to have faster mobility decline, but this effect was statistically and clinically small. FUNDING: TILDA is funded by Atlantic Philanthropies, the Irish Department of Health and Irish Life. Roman Romero-Ortuno is funded by Science Foundation Ireland (grant number 18/FRL/6188).